Preservice Teachers' Mental Health: Using Student Voice to Inform Pedagogical, Programmatic, and Curricular Change. (3rd July 2022) - Ressler, Mary Beth; Apantenco, Cynthia; Wexler, Lindsay; King, Kathleen
ABSTRACT: The purpose of the study is to analyze the role preservice teachers' mental health plays in their development during teacher preparation programs and the role of teacher preparation programs in preservice teachers' mental health journeys. Using an ethic of care theoretical approach, a within-method triangulation designwas utilized with interviews, focus groups, and surveys in a qualitative study with 33 participants in order to more fully understand student participant perspectives. The major findings included the need to better normalize mental healthcare, the demand preservice teachers face preparing for a helping profession, and the importance of providing an environment in which care and self-care can be better developed.